Role of Informed Consent in India Past, Present and Future Trends - Yadav, Mukesh; Thakur, Pramendra Singh; Rastogi , Pooja (Journal of Indian Academy of Forensic Medicine, 2015)
There is a need to keep the cost of treatment within affordable limits. Bringing in the American concepts and standards of treatment procedures and disclosure of risks, consequences and choices will inevitably bring in higher cost-structure of treatment. Patients in India cannot afford them. People in India still have great regard and respect for Doctors. The Members of medical profession have also, by and large, shown care and concern for the patients. There is an atmosphere of trust and implicit faith in the advice given by the Doctor. Apex Court observed that “What choice do these poor patients have? Any treatment of whatever degree is a boon or a favour, for them. The stark reality is that for a vast majority in the country, the concepts of informed consent or any form of consent, and choice in treatment, have no meaning or relevance.” This paper deals with the applicability of concept of ‘informed consent’ in past, present and future scenario in India, based on the critical review of recent decisions of Hon’ble Supreme Court of India and National Consumer Dispute Redressal Commission, New Delhi.